Design of a measurement system for use in static balancing a two-axis gimbaled antenna. (November 2014) - Yan, WX; Zhan, ST; Qian, ZY; Fu, Z; Zhao, YZ
The two-axis gimbaled antenna's performance can be greatly improved if it is statically balanced. This paper intends to present a novel design of a measurement system for use in statically balancing a two-axis gimbaled antenna mounted on an aircraft. The details of the measurement system and its working principle are explained, including the dynamics of the two-degree-of-freedom flexure-hinge leverage and the control configuration of the measurement system. The measurement principle is proposed after the theoretical measurement uncertainties estimated and the key factors that determine the measurement accuracy are found. By controlling the uncertainty induced from the major factors, the measurement accuracy can be finally controlled. The measurement result is proved sufficiently accurate by means of High-speed centrifuge method.